Joint coordination contract for capital‐constrained supply chains under asymmetric information. (1st July 2022) - Yan, Bo; Liu, Yanping; Jin, Zijie
Abstract : A two‐echelon supply chain considering capital constraints and asymmetric information is established. The supplier provides credit guarantees for the capital‐constrained retailer to loan from the bank, and its information about the retailer's capital type is asymmetric. The equilibrium decisions of supply chain participants are analyzed by using the Stackelberg game theory and principal–agent theory. Then, a joint contract is designed to eliminate the double marginalization effect. The results show that the supplier and the bank make different decisions for different types of retailers to avoid adverse selection. The joint contract of revenue‐sharing and transfer payment can coordinate the supply chain.